1994
DOI: 10.2991/jnmp.1994.1.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry reduction and exact solutions of the Navier-Stokes equations. II

Abstract: 6 Symmetry properties and exact solutions of system (3.12)As was mentioned in Sec. 3, ansatzes (3.4)-(3.7) reduce the NSEs (1.1) to the systems of PDEs of a similar structure that have the general form (see (3.12)):

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 9 publications
0
34
0
Order By: Relevance
“…[12], [37] and the review [40]). But, at best of our knowledge, no examples of solutions in R 3 with fast decay of the energy have been constructed so far.…”
Section: Introductionmentioning
confidence: 99%
“…[12], [37] and the review [40]). But, at best of our knowledge, no examples of solutions in R 3 with fast decay of the energy have been constructed so far.…”
Section: Introductionmentioning
confidence: 99%
“…If the basis of S does not depend on arbitrary functions (all functions in (3) are specified), then the coordinates of operator X and constants b l i will be the only unknown quantities in Eq. (4). Note that these equations may be both algebraic and differential.…”
Section: Normalizer Calculation and Classification Problemmentioning
confidence: 96%
“…Classification of infinite-dimensional subalgebras of this algebra was studied in [6]. 3 Short reviews devoted to invariant solutions of the Navier-Stokes equations can be found in [14][15][16]. 4 Firstly the approach of partially invariant solutions to the NavierStokes equations was applied in [17].…”
Section: The Reduction Of the Navier-stokes Equationsmentioning
confidence: 99%